2015
DOI: 10.7566/jpsj.84.054709
|View full text |Cite
|
Sign up to set email alerts
|

Possible Excitonic Phase of Graphite in the Quantum Limit State

Abstract: The in-plane resistivity, Hall resistivity and magnetization of graphite were investigated in pulsed magnetic fields applied along the c-axis. The Hall resistivity approaches zero at around 53 T where the in-plane and out-of-plane resistivities steeply decrease. The differential magnetization also shows an anomaly at around this field with a similar amplitude compared to that of de Haas-van Alphen oscillations at lower fields. This transition field appears insensitive to disorder, but reduces with doping holes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 28 publications
6
70
2
Order By: Relevance
“…Currently, reports support different hypothesis, which include the formation of a CDW, a spin-density wave or the opening of an excitonic gap. All expected to occur along graphite's c-axis at the lowest Landau level [9,10,14,15,16]. Different approaches to understand the nature of the HRS have been attempted in the past decades, highlighting various aspects of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, reports support different hypothesis, which include the formation of a CDW, a spin-density wave or the opening of an excitonic gap. All expected to occur along graphite's c-axis at the lowest Landau level [9,10,14,15,16]. Different approaches to understand the nature of the HRS have been attempted in the past decades, highlighting various aspects of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, attempts in this topic are currently carried out by performing ionic implantation in bulk graphite or testing different sample qualities. These approaches do not allow one to reliably separate the effects caused by induced disorder from the ones caused by the intended doping [11,14]. This becomes critical when comparing different samples, as differences on disorder and native charge carrier concentration can affect the phenomenon under consideration, causing seemingly similar experiments to produce potentially diverging conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…So far attempts to directly measure the gap of this putative density wave spectroscopically [28,29] Recently, Fauqué et al [12] discovered the onset of a second density-wave anomaly above 53 T, by out-of-plane transport measurements on Kish graphite up to 80 T. This state was found to collapse at 75 T into a state with metallic c-axis conductivity. These authors argued that only one of the (0; ↑) or (−1; ↓) LLs depopulates at 53 T, and, furthermore, that the (0; ↓) and (−1; ↑) levels remain populated above 75 T. On the other hand, the observation of a vanishing Hall coefficient at 53 T [30] was interpreted in terms of the depopulation of both the (0; ↑) and (−1; ↓) LLs at 53 T, as predicted theoretically [25]. It was suggested that an excitonic phase forms in the remaining (0; ↓) and (−1; ↑) levels above 53 T. Elsewhere it has been argued that an excitonic insulator phase appears at 46 T [31].…”
mentioning
confidence: 99%
“…Recently, a comprehensive resistivity measurement in graphite under high magnetic field has been carried out up to 90 T 12 . The graphite under the high magnetic field (the field ⊥ the graphene plane) exhibits consecutive metal-insulator transitions as well as insulator-metal re-entrant transition at low temperature in an electric resistivity along the out-of-plane (field) direction [10][11][12][13]15,53 .…”
Section: Summary and Discussion On Experimentsmentioning
confidence: 99%
“…Since the excitonic pairing is between ↑ spin electron-type band and ↓ spin holetype band, the transport must be free from pinning effect due to charged impurities 61 . Thereby, we can expect that such EI phase with broken translational symmetries within the xy plane may give a simple theory explanation for the in-plane metallic bulk-transport behaviour in the second 'insulating' phase of 53 T < H < 75 T in the graphite experiment [10][11][12]15 . In fact, the recent transport experiment up to 90 T shows that the in-plane resistivity in the second 'insulating' phase is nearly constant in the field 12 .…”
Section: Summary and Discussion On Experimentsmentioning
confidence: 99%